Biodegradation of Paraffin in Crude Oil: Prevention of Wax Deposition - Liu, Jianghong; Jia, Yunpeng; Xu, Ruidan (Asian Journal of Chemistry, 2013)
Microorganisms were obtained by separation and purification experiment from waxy oil production wells in Jilin oil field. The paraffin-degrading strain was identified as Bacillus sp.. After microbial treatment, the paraffin degradation rate could reach to 79.3 %, the paraffin prevention rate could reach to 68.4 %, the reduction rate of crude oil viscosity was 56.1 %, the oil freezing point reduced by 5.5 ºC and the reduction rate of culture surface tension was 46.3 %. By analyzing the data, the paraffin-degrading strain has better effect on microbial prevention of wax deposition.